The Comparison of Knowledge Level and Awareness of Osteoporosis between Women and Men - Ebru Altın; Bahar Karadeniz; Fatma Türkyön (Galenos Yayinevi, 2014)
Objective: Osteoporosis is a disease which causes fractures depending on decreasing bone mineral density. Nutrition and life style which support the bone health must be known for prevention of the disease. This study was conducted to assess awareness about OP between men and women. Materials and Methods: The study was performed between the dates November 2012-May 2014 in Denizli Pamukkale University. A form including sociodemographic features, Osteoporosis Knowledge Test (OKT) and Osteoporosis Health Belief Scale (OHBS) were used in the collection of the data for evaluation the osteoporosis knowledge level and awarenes of the volunteers who accept to attend the study. Results: Hundred forty-seven volunteers of 96 women and 51 men attended to the study. Mean age was 36.1±14,6 years and 6.1% of the participants had a diagnosis osteoporosis and 13.6% of the participants had a family history of osteoporosis. When the participants were compared according to gender, there were statistically significant difference between two groups for education level, had own and a family history of osteoporosis (p<0,05). Men had higher education level than the women group. Women have higher own and familiy history of osteoporosis. When the scores of the questionnaires were compared between women and men, the mean score of the Osteoporosis Health Belief Scale- Susceptibility score was 16.8±5.0 and 13.7±4.0, respectively. The women's score were higher than men (p<0.05). Significant difference wasn't found in the other subscales. Conclusion: Despite the high educational level of the men, it was detected that the level of the osteoporosis susceptibility was lower than women. High Osteoporosis Health Belief Scale level of women shows that women think osteoporosis is serious illness. Since the basic treatment approach was the prevention for osteoporosis, the education programs must be organized for either women who have high risk, or also for men to improve the awareness. (Turkish Journal of Osteoporosis 2014;20: 98-103)